High-density amorphous ice: nucleation of nanosized low-density amorphous ice. (21st December 2017) - Tonauer, Christina M; Seidl-Nigsch, Markus; Loerting, Thomas
Abstract: The pressure dependence of the crystallization temperature of different forms of expanded high-density amorphous ice (eHDA) was scrutinized. Crystallization at pressures 0.05–0.30 GPa was followed using volumetry and powder x-ray diffraction. eHDA samples were prepared via isothermal decompression of very high-density amorphous ice at 140 K to different end pressures between 0.07–0.30 GPa (eHDA 0.07–0.3 ). At 0.05–0.17 GPa the crystallization line T x ( p ) of all eHDA variants is the same. At pressures  >0.17 GPa, all eHDA samples decompressed to pressures  <0.20 GPa exhibit significantly lower T x values than eHDA 0.2 and eHDA 0.3 . We rationalize our findings with the presence of nanoscaled low-density amorphous ice (LDA) seeds that nucleate in eHDA when it is decompressed to pressures  <0.20 GPa at 140 K. Below ~0.17 GPa, these nanosized LDA domains are latent within the HDA matrix, exhibiting no effect on T x of eHDA <0.2 . Upon heating at pressures  ⩾0.17 GPa, these nanosized LDA nuclei transform to ice IX nuclei. They are favored sites for crystallization and, hence, lower T x . By comparing crystallization experiments of bulk LDA with the ones involving nanosized LDA we are able to estimate the Laplace pressure and radius of ~0.3–0.8 nm for the nanodomains of LDA. The nucleation of LDA in eHDA revealed here is evidence for the first-order-like nature of the HDA  →  LDA transition, supporting water's liquid–liquid transition scenarios.